cDNA sequences of Torpedo marmorata acetylcholinesterase: primary structure of the precursor of a catalytic subunit; existence of multiple 5'-untranslated regions. - Sikorav, J L (1987)
cDNA clones coding for a catalytic subunit of acetylcholinesterase were isolated from cDNA libraries constructed from Torpedo marmorata electric organ. The nucleotide sequence of the cloned cDNAs codes for a 599-amino acid precursor containing a 24-amino acid signal peptide. This primary structure has been compared with the sequences of Torpedo californica and Drosophila melanogasta acetylcholinesterases, and with that of human butyrylcholinesterase. Genomic blot experiments carried out with cDNA restriction fragments used as hybridization probes are in agreement with the existence of a single gene coding for the different catalytic subunits of Torpedo acetylcholinesterase. Unexpectedly, we observed multiple 5'-untranslated regions, which may contain several initiation codons.